Intergroup contact as predictor of in-group bias and outgroup discrimination - Jelić, Margareta (Array, 2005)
The contact hypothesis is considered one of most effective strategies for improving intergroup relations and reducing prejudice. Research done so far showed that intergroup friendships are associated with less ethnic prejudice and less in-group bias. The goal of this research was to test the contact hypothesis in a real life situation, namely on two conflicted ethnic groups living in the same community. In other words, we wanted to investigate whether contact with the outgroup remains the most important predictor of in-group bias and outgroup discrimination even in a context where two groups are in conflict and their national identity is very salient in everyday life. Results suggest that the quality of contact with the outgroup is negatively correlated with in-group bias, outgroup discrimination and national identification level. Furthermore, weaker contact and national identification proved to be most important predictors of in-group bias and outgroup discrimination.